Prevalence and correlates of electronic cigarette use among adolescents in Greece: A preliminary cross-sectional analysis of nationwide survey data. (December 2015) - Fotiou, Anastasios; Kanavou, Eleftheria; Stavrou, Myrto; Richardson, Clive; Kokkevi, Anna
Abstract: Introduction: This study reports the prevalence of electronic cigarette (e-cigarette) use among adolescents in Greece and explores how dual smokers of e-cigarettes and combustible (conventional) cigarettes differ from smokers of only combustible cigarettes across socio-demographic, familial, psychosomatic health and substance use characteristics. Methods: Self-reports on smoking were collected from a nationally representative sample of 1320 15-year-old Greek students in the 2014 Health Behaviour in School-aged Children study. Bivariate and multivariable logistic regression analyses were carried out with dependent variables a) lifetime smoking conventional cigarettes and b) lifetime e-cigarette use among lifetime smokers. Results: About 36.9% of 15-year-olds reported lifetime smoking of conventional cigarettes, and 16.6% lifetime use of e-cigarettes, mostly experimenting (0.5% reported current e-cigarette use). Six in 7 ever e-cigarette smokers had smoked conventional cigarettes. Peers who smoke and lifetime cannabis use were significant correlates of both lifetime conventional cigarette and e-cigarette smoking, but more strongly for smoking conventional cigarettes. Alcohol use and low parental monitoring correlated with tobacco smoking but not e-cigarette use. Girls were more likely than boys to report lifetime use of tobacco, but, among lifetime smokers, boys had almost seven times the odds of girls of e-cigarette use. In lifetime smokers, low life satisfaction in females and current smoking of conventional tobacco were independently associated with the experimentation with e-cigarettes. Conclusions: Experimental use of e-cigarettes is relatively widespread among adolescents in Greece. Targeted interventions should focus on male smokers and the role of peer processes and cannabis use in the risk of experimenting with e-cigarettes. Highlights: We studied correlates of tobacco and e-cigarette use in adolescents in Greece. Female gender is associated with using tobacco, but male gender with e-cigarettes. E-cigarette use is associated with current but not with heavy smoking. Alcohol and low parental monitoring correlate with tobacco but not e-cigarettes. Cannabis and peer smoking correlate strongly with tobacco, less with e-cigarettes.